Legislative support of the Internal Affairs and the Interior Troops agencies in territorial defense - Butkevich S. А.; Yevsyukova Ya. І. (Honor and Law, 2019)
Legislative support of routine and combat activity of the Internal Affairs and the Interior Troops agencies of Ukraine and Commonwealth of Independent States countries-participants as for the organization and realization of actions in territorial defense is considered. The ways of increasing this activity efficiency in the particular sector of national security are determined.